2011
DOI: 10.17221/394/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Contents of sulforaphane and total isothiocyanates, antimutagenic activity, and inhibition of clastogenicity in pulp

Abstract: Totušek J., Tříska J., Lefnerová D., Strohalm J., Vrchotová N., Zendulka O., Průchová J., Chaloupková J., Novotná P., Houška M. (2011): Contents of sulforaphane and total isothiocyanates, antimutagenic activity, and inhibition of clastogenicity in pulp juices from cruciferous plants. Czech J. Food Sci., 29: 548-556.The consumption of Cruciferous vegetables is important for the prevention of cancerous diseases, particularly colorectal cancer. The effects of technological treatments (freezing, pasteurisation, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
2
10
0
1
Order By: Relevance
“…This communication describes the preparation of juices from red beet, celery, parsnip, broccoli, carrot, sauerkraut, and other vegetables that are inexpensive, locally available all the year round and have relatively stable quality (Houška et al 2007;Totušek et al 2011).…”
Section: Mixed Vegetable Juices Acidified With Sauerkraut Juice and Pmentioning
confidence: 99%
“…This communication describes the preparation of juices from red beet, celery, parsnip, broccoli, carrot, sauerkraut, and other vegetables that are inexpensive, locally available all the year round and have relatively stable quality (Houška et al 2007;Totušek et al 2011).…”
Section: Mixed Vegetable Juices Acidified With Sauerkraut Juice and Pmentioning
confidence: 99%
“…Cauliflower has become one of the main vegetables grown in Brazil probably due to its recognition as a functional food, acting mainly on cancer prevention (Totušek et al, 2011) due to the presence of antioxidants and high concentrations of vitamins (Soegas et al, 2011). Nitrogen is a precursor of these substances (Schumacher et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Isothiocyanate content in broccoli juice treated by freezing, pasteurization and high pressure was found to range from 1.45 to 10.68, 1.94 to 5.54 and 1.87 to 11.27 μmol/l, respectively (Totušek et al 2011 ). Sulforaphane content in broccoli juice treated by freezing, pasteurization and high pressure was found to range from 7.77 to 14.25, 8.87 to 15.67 and 8.24 to 14.64 μg/ml, respectively.…”
Section: Processing / Storage and Broccoli Phytochemicalsmentioning
confidence: 96%
“…The results of this study indicated the presence of potent antigenotoxic factors in broccoli. In the Ames mutagenic test using Salmonella typhimurium TA 100, high pressure or freezing treatment of broccoli juice exerted strongly positive test MNU (2-nitroso-2-methylurea) mutagen inhibition (Totušek et al 2011 ). In the Ames mutagenic test using Salmonella typhimurium TA 98, high pressure or freezing treatment of broccoli juice exerted strongly positive test on IQ (2-amino-3-methyl-3H-imi-dazo-[4,5-f ]quinoline) mutagen inhibition.…”
Section: Antimutagenic / Anticlastogenic Activitiesmentioning
confidence: 99%